A kind of detachable polyurethane heat-conducting structural adhesive and preparation method thereof
By introducing phase change resin and thermal powders of different particle sizes into the polyurethane thermally conductive structural adhesive, adjusting its bonding strength and thermal conductivity, the problem of difficult disassembly of polyurethane thermally conductive structural adhesive in the battery system is solved, and detachability and high efficiency are achieved Thermal conduction effect.
Patent Information
- Application Number
- CN202310188329.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-28
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-02-28
AI Technical Summary
The existing polyurethane thermal structural adhesive is difficult to disassemble during the remediation process of new energy battery systems, resulting in environmental pollution and energy waste.
The thermally conductive resin part and the thermally conductive curing agent part are respectively composed of the resin mixture and the first thermally conductive filler, as well as the curing agent mixture and the second thermally conductive filler. By introducing a phase change resin and a thermally conductive powder of different particle sizes, the bonding of the structural glue is adjusted. Strength and thermal conductivity for detachability.
Under the phase change temperature of the phase change resin, the difficulty of peeling the polyurethane thermally conductive structural adhesive is reduced, the difficulty of disassembly of the battery pack is solved, the battery recycling work is promoted, and the thermal conductivity of the structural adhesive is improved.
Smart Images

Figure CN116285855B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyurethane heat-conducting structural adhesive, and in particular to a detachable polyurethane heat-conducting structural adhesive and a preparation method thereof. Background Art
[0002] Polyurethane is the abbreviation of polyurethane, and its English name is polyurethane. It is an emerging organic polymer material and is known as the "fifth plastic". Due to its excellent performance, it is widely used in many fields of the national economy. Its product applications involve light industry, chemical industry, electronics, textiles, medical treatment, construction, building materials, automobiles, national defense, aerospace and aviation.
[0003] Polyurethane structural adhesive has strong adhesion and lower hardness than traditional epoxy resin adhesive. At the same time, the polyurethane thermal conductive structural adhesive formed by adding thermal conductive filler to the polyurethane structural adhesive has better thermal conductivity. Therefore, this type of polyurethane structural adhesive is often used in new energy battery systems, which effectively improves the bonding strength between the battery pack and the water cooling plate and plays a role in heat dissipation of the battery system, so that the stability of the entire battery pack is guaranteed.
[0004] However, during the repair process of new energy battery systems, the high bonding strength of polyurethane structural adhesives makes it difficult to disassemble the batteries, causing environmental pollution and energy waste. Therefore, it is urgent to provide a solution to improve this problem. Summary of the invention
[0005] The purpose of the present invention is to provide a detachable polyurethane thermal conductive structural adhesive and a preparation method thereof, which can maintain the bonding strength and be easy to peel off when disassembly is required, thereby facilitating the disassembly of items bonded with the polyurethane structural adhesive.
[0006] The present invention provides a detachable polyurethane thermal conductive structural adhesive adopts the following technical solution:
[0007] It includes a thermally conductive resin part and a thermally conductive curing agent part, wherein the thermally conductive resin part includes a resin mixture and a first thermally conductive filler, the thermally conductive curing agent includes a curing agent mixture and a second thermally conductive filler, and the volume ratio of the thermally conductive resin part to the thermally conductive curing agent part is 9 / 10-10 / 9;
[0008] The resin mixture includes a phase change resin, a catalyst and a hydroxy resin M, and the phase change resin accounts for 24-52% by weight of the resin mixture;
[0009] The curing agent mixture comprises a hydroxy resin N and a chain extender, and the hydroxy resin N accounts for 50-90% by weight of the curing agent mixture.
[0010] By adopting the above technical scheme, the present application introduces phase change resin into the thermally conductive resin part, and adds a first thermally conductive filler and a second thermally conductive filler into the thermally conductive resin part and the thermally conductive curing agent part respectively, so that the obtained structural adhesive has better thermal conductivity effect. When the phase change temperature of the phase change resin is reached, the phase change resin liquefies and penetrates the bonding surface, thereby reducing the bonding strength between the structural adhesive and the bonding surface. The difficulty of peeling off the polyurethane thermally conductive structural adhesive can be greatly reduced at the phase change temperature of the phase change resin, thereby solving the problem of difficulty in disassembling existing battery packs and effectively promoting battery recycling.
[0011] Optionally, the phase change temperature of the phase change resin is 80-150°C.
[0012] Optionally, the phase change resin is one or more of phase change polyolefin and phase change paraffin.
[0013] Optionally, the number average molecular weight of the phase change polyolefin is 2000-5000.
[0014] Optionally, the hydroxy resin N is one or more of polyether polyol, polyester polyol, castor oil, modified castor oil and sorbitol.
[0015] Optionally, the chain extender is an isocyanate chain extender, and the isocyanate chain extender is selected from one or more of diphenylmethane diisocyanate, isophorone diisocyanate, polyisocyanate and hexamethylene diisocyanate.
[0016] Optionally, the catalyst is one or more of an organic tin catalyst, an organic zinc catalyst, an aliphatic amine catalyst, an alicyclic amine catalyst, an alcohol compound catalyst, and an aromatic amine catalyst. The addition of the catalyst can accelerate the reaction rate of the thermally conductive resin part and the thermally conductive curing agent part, thereby reducing the curing reaction time.
[0017] Optionally, in terms of weight percentage of the thermally conductive resin portion, the resin mixture accounts for 3-19%, and the first thermally conductive filler accounts for 81-97%; in terms of weight percentage of the thermally conductive curing agent portion, the curing agent mixture accounts for 7-27%, and the second thermally conductive filler accounts for 73%-93%.
[0018] By adopting the above technical solution, the obtained polyurethane thermal conductive structural adhesive has a better thermal conductivity effect, which effectively reduces the problem of electronic components being burned out due to the inability to quickly dissipate heat.
[0019] Optionally, the first thermally conductive filler and the second thermally conductive filler both include thermally conductive powders with two different particle sizes, and the particle size of one thermally conductive powder is 7-14 times that of the other thermally conductive powder.
[0020] By matching thermally conductive powders of different particle sizes, the mixing effect of the first thermally conductive filler in the thermally conductive resin part and the second thermally conductive filler in the thermally conductive curing agent part is optimized, the thermal conductivity of the structural adhesive is improved, heat is quickly dissipated during application, and it is beneficial to the stripping operation during disassembly and recycling.
[0021] Optionally, the thermally conductive powder is selected from one or more of aluminum hydroxide, aluminum oxide, boron nitride and aluminum nitride.
[0022] Optionally, the first thermally conductive filler further includes 0.14-0.16% of a first coupling agent, based on the weight percentage of the thermally conductive resin portion; and the second thermally conductive filler further includes 0.14-0.16% of a second coupling agent, based on the weight percentage of the thermally conductive curing agent portion.
[0023] Optionally, the first coupling agent and the second coupling agent are both selected from one or more of octyltrimethoxysilane, decyltrimethoxysilane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane and 3-glycidyloxypropyltrimethoxysilane.
[0024] In a second aspect, the present invention further provides a method for preparing a detachable polyurethane thermally conductive structural adhesive, comprising the following steps:
[0025] Mixing the hydroxy resin M, the phase change resin and the catalyst to prepare a resin mixture;
[0026] Mixing the resin mixture with the first thermally conductive filler to prepare a thermally conductive resin part;
[0027] Mixing the hydroxy resin N and the chain extender to prepare a curing agent mixture;
[0028] mixing the curing agent mixture with the second thermally conductive filler to prepare a thermally conductive curing agent part;
[0029] The thermally conductive resin part and the thermally conductive curing agent part are mixed in a volume ratio of 9 / 10-10 / 9 to prepare a detachable polyurethane thermally conductive structural adhesive.
[0030] The beneficial effects of a detachable polyurethane thermally conductive structural adhesive proposed by the present invention are as follows: a hydroxyl resin M, a phase change resin and a catalyst are pre-mixed to improve the dispersion uniformity of the phase change resin in the resin mixture, and then mixed with a first thermally conductive filler to prepare a thermally conductive resin part. While preparing the thermally conductive resin part, a thermally conductive curing agent part can be prepared to shorten the reaction time; the hydroxyl resin N is pre-polymerized with a chain extender to prepare a curing agent mixture, and then the curing agent mixture is mixed with a second thermally conductive filler to prepare a thermally conductive curing agent part, which can reduce the content of isocyanate in the thermally conductive curing agent part and adjust the hardness of the prepared polyurethane thermally conductive structural adhesive.
[0031] Optionally, during the step of mixing the hydroxy resin N and the chain extender to prepare a curing agent mixture, the hydroxy resin N and the chain extender are mixed evenly and then stirred at a constant temperature for reaction.
[0032] Optionally, during the constant temperature stirring reaction, the constant temperature stirring reaction temperature is controlled to be 70-85° C., and the constant temperature stirring reaction time is controlled to be 2-3 h. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The present invention is a flowchart of a method for preparing a detachable polyurethane thermally conductive structural adhesive according to an embodiment of the present invention. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be understood by people with general skills in the field to which the present invention belongs. "Including" and similar words used in this article mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, without excluding other elements or objects.
[0035] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range limited by a series of upper preferred values and lower preferred values, this should be understood to specifically disclose all ranges formed by any pairing of any upper range limit or preferred value with any lower range limit or preferred value, regardless of whether the range is disclosed separately. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0036] Example
[0037] Examples 1-8
[0038] The weight proportions of the components of the detachable polyurethane thermal conductive structural adhesive in Examples 1-8 of the present invention are shown in Table 1.
[0039] Table 1 Weight percentage of each component of the detachable polyurethane thermal conductive structural adhesive in Examples 1-8 of the present invention
[0040]
[0041]
[0042] In the resin mixtures of Examples 1, 3, 5 and 7, the hydroxy resin M used is castor oil, specifically selected from refined castor oil of Mingjing Chemical; the phase change resin used is a phase change polyolefin, the phase change temperature of which is 150° C., specifically selected from ExxonMobil TM LLDPE LL 1004YB; the catalyst used is an organic zinc catalyst, specifically zinc isooctanoate.
[0043] In the resin mixture of Examples 2, 4, 6 and 8, the hydroxyl resin M used is a polyether polyol, specifically a polyether polyol produced by Shandong Bluestar Dongda Chemical Co., Ltd. with the brand name DL-2000, the number average molecular weight of which is 2000 and the functionality is 2; the phase change resin used is a phase change paraffin wax, the phase change temperature of which is 80°C, specifically a phase change paraffin wax produced by Shanghai Joule Wax Co., Ltd. with the brand name PCM-80; the catalyst used is an organic tin catalyst, specifically dibutyltin dilaurate.
[0044] The first coupling agent used in Example 1, Example 3, Example 5 and Example 7 is dodecyltrimethoxysilane. The thermally conductive powder is put into a high-speed disperser, the first coupling agent is added, and the mixture is dispersed for 2 hours to obtain a first thermally conductive filler. The second coupling agent used is dodecyltrimethoxysilane. The thermally conductive powder is put into a high-speed disperser, the second coupling agent is added, and the mixture is dispersed for 2 hours to obtain a second thermally conductive filler.
[0045] The first coupling agent used in Example 2, Example 4, Example 6 and Example 8 is octyltrimethoxysilane; the second coupling agent used is octyltrimethoxysilane.
[0046] In the curing agent mixture of Examples 1, 2, 5 and 6, the hydroxy resin N used is a polyether polyol, specifically a polyether polyol produced by Shandong Bluestar Dongda Chemical Co., Ltd., with a brand name of DL-2000, and the number average molecular weight of the polyether polyol is 2000 and the functionality is 2.
[0047] In the curing agent mixtures of Examples 3, 4, 7 and 8, the hydroxy resin N used is castor oil, specifically, the refined castor oil selected from Mingjing Chemical.
[0048] In the curing agent mixtures of Examples 1, 3, 5 and 7, the chain extender used is an isocyanate chain extender, specifically diphenylmethane diisocyanate.
[0049] In the curing agent mixtures of Examples 2, 4, 6 and 8, the chain extender used is an isocyanate chain extender, specifically crude MDI (crude isocyanate product, purchased from Yantai Wanhua Chemical Co., Ltd.).
[0050] In the first thermally conductive filler of Embodiments 1 to 4, the thermally conductive powder is a mixture of 70 μm aluminum hydroxide and 5 μm aluminum hydroxide in a weight ratio of 1:1.
[0051] In the first thermally conductive filler of Examples 5 to 8, the thermally conductive powder is a mixture of 50 μm aluminum hydroxide and 1 μm aluminum hydroxide in a weight ratio of 1:1.
[0052] In the second thermally conductive filler of Examples 1 to 4, the thermally conductive powder is a mixture of 70 μm aluminum hydroxide and 5 μm aluminum hydroxide in a weight ratio of 1:1.
[0053] In the second thermally conductive filler of Examples 5 to 8, the thermally conductive powder is a mixture of 50 μm aluminum hydroxide and 1 μm aluminum hydroxide in a weight ratio of 1:1.
[0054] See also Figure 1 The preparation method of the detachable polyurethane thermal conductive structural adhesive in the present embodiment 1-8 comprises the following steps:
[0055] The hydroxy resin M, the phase change resin and the catalyst are put into a mixer and mixed evenly to obtain a resin mixture;
[0056] Mixing the first thermally conductive filler with the resin mixture to obtain a thermally conductive resin part;
[0057] The hydroxy resin N and the chain extender are put into a stirrer and mixed evenly, and after stirring for 2.5 hours in a constant temperature environment of 80°C, a curing agent mixture is obtained by reaction;
[0058] The second thermally conductive filler is mixed with the curing agent mixture to obtain a thermally conductive curing agent part;
[0059] When in use, the thermally conductive resin part and the thermally conductive curing agent part are mixed and reacted to obtain a detachable polyurethane thermally conductive structural adhesive, and the volume ratio of the thermally conductive resin part to the thermally conductive curing agent part is controlled to be 1:1.
[0060] In some other embodiments, the thermally conductive resin portion and the thermally conductive curing agent are mixed and reacted in a volume ratio of 9 / 10-10 / 9 to prepare the detachable polyurethane thermally conductive structural adhesive.
[0061] In some other embodiments, the thermally conductive resin portion includes 3-19% of the resin mixture and the remainder of the first thermally conductive filler, based on the weight percentage of the thermally conductive resin portion.
[0062] In some other embodiments, the resin mixture includes 24-52% of the phase change resin, 0.04-0.62% of the catalyst, and the balance of the hydroxyl resin M, based on the weight percentage of the resin mixture.
[0063] In some other embodiments, the phase change resin is one or more of phase change polyolefin and phase change wax.
[0064] In some other embodiments, the phase change polyolefin has a number average molecular weight of 2000-5000.
[0065] In some other embodiments, the phase change temperature of the phase change resin is 80-150°C.
[0066] In some other embodiments, the catalyst is one or more of an organic tin catalyst, an organic zinc catalyst, an aliphatic amine catalyst, an alicyclic amine catalyst, an alcohol compound catalyst and an aromatic amine catalyst.
[0067] In some other embodiments, the aliphatic amine catalyst is one or more of N,N-dimethylcyclohexane, bis(2-dimethylaminoethyl) ether, N,N,N',N'-tetramethylalkylenediamine, triethylamine and N,N-dimethylbenzylamine.
[0068] In some other embodiments, the alicyclic amine catalyst is one or more of solid amine, N-ethylmorpholine, N,N'-dimethylformamide (NMM) and N,N'-diethylpiperazine.
[0069] In some other embodiments, the organic zinc catalyst is one or more of zinc cyclohexaneate, zinc isooctanoate, di(pentamethylcyclopentadienyl)zinc, zinc gluconate, zinc methionine, zinc neodecanoate, zinc acetate, and zinc carboxylates.
[0070] In some other embodiments, the aromatic amine catalyst is one or more of pyridine and N,N'-dimethylpyridine.
[0071] In some other embodiments, the alcohol compound catalyst includes one or more of triethanolamine and DMEA.
[0072] In some other embodiments, the hydroxy resin M is one or more of polyether polyol, polyester polyol, castor oil, modified castor oil and sorbitol.
[0073] In some other embodiments, when the hydroxy resin M is modified castor oil, AC-009 produced by Ito Oil Manufacturing Co., Ltd. is used.
[0074] In some other embodiments, the first thermally conductive filler and the second thermally conductive filler both include thermally conductive powders of two different particle sizes, and the particle size of one thermally conductive powder is 7-14 times that of the other thermally conductive powder.
[0075] In some other embodiments, the thermally conductive powder in the first thermally conductive filler and the second thermally conductive filler is selected from one or more of aluminum hydroxide, aluminum oxide, boron nitride and aluminum oxide.
[0076] In some other embodiments, the particle sizes of the thermally conductive powder in the first thermally conductive filler and the second thermally conductive filler are both smaller than 75 μm.
[0077] In some other embodiments, the hydroxy resin N is one or more of polyether polyol, polyester polyol, castor oil, modified castor oil and sorbitol.
[0078] In some other embodiments, when the hydroxy resin N is modified castor oil, AC-009 produced by Ito Oil Manufacturing Co., Ltd. can be selected.
[0079] In some other embodiments, preparing the detachable polyurethane thermal conductive structural adhesive comprises the following steps:
[0080] Mixing the hydroxy resin M, the phase change catalyst and the catalyst to prepare a resin mixture;
[0081] Mixing the resin mixture with the first thermally conductive filler to prepare a thermally conductive resin part;
[0082] Mixing the hydroxy resin N and the chain extender to prepare a curing agent mixture;
[0083] mixing the curing agent mixture with the second thermally conductive filler to prepare a thermally conductive curing agent part;
[0084] The thermally conductive resin part and the thermally conductive curing agent part are mixed in a volume ratio of 9 / 10-10 / 9 to prepare a detachable polyurethane thermally conductive structural adhesive.
[0085] In some other embodiments, during the step of mixing the hydroxyl resin N and the chain extender to prepare the curing agent mixture, the hydroxyl resin N and the chain extender are mixed evenly and then stirred at a constant temperature for reaction.
[0086] In some other embodiments, during the constant temperature stirring reaction, the constant temperature stirring reaction temperature is controlled to be 70-85° C., and the constant temperature stirring reaction time is controlled to be 2-3 h.
[0087] Comparative Example
[0088] Comparative Example 1
[0089] A polyurethane thermally conductive structural adhesive in this comparative example 1 is formed by mixing a thermally conductive resin part and a thermally conductive curing agent part in a volume ratio of 1:1;
[0090] The thermally conductive resin part includes 19 parts of castor oil and 0.08 parts of an organic zinc catalyst in parts by weight;
[0091] The thermal conductive curing agent part includes 12.8 parts of polyether polyol and 3.2 parts of diphenylmethane diisocyanate by weight.
[0092] The preparation method of the polyurethane thermal conductive structural adhesive in Comparative Example 1 comprises the following steps:
[0093] The castor oil and the organic zinc catalyst are mixed evenly to prepare the thermal conductive resin part;
[0094] The polyether polyol and diphenylmethane diisocyanate are reacted in an environment of 80° C. for 2.5 hours to obtain a thermally conductive curing agent part;
[0095] When in use, the heat-conducting resin part and the heat-conducting curing agent part are evenly mixed in a volume ratio of 1:1 to obtain the polyurethane heat-conducting structural adhesive.
[0096] Performance Testing
[0097] The polyurethane thermal conductive structural adhesives in Examples 1-8 and Comparative Example 1 were tested as follows:
[0098] Thermal conductivity, in W / mK, based on ASTM D5470;
[0099] Hardness (Shore D), according to GB / T 2411;
[0100] Tensile shear strength, in MPa, based on ISO 4587-2003;
[0101] 25℃, T peel strength, unit is N / mm, based on GB / T 2791-1995;
[0102] 150℃, T peel strength, unit is N / mm, based on GB / T 2791-1995;
[0103] The polyurethane thermal conductive structural adhesives in Examples 1-8 and Comparative Example 1 were made into test specimens according to the test standards of each test item, placed in an environment of 25° C. for curing for 7 days, and then tested. The test results are shown in Table 2.
[0104] Table 2 Test items and data of polyurethane thermal conductive structural adhesive in Examples 1-8 and Comparative Example 1
[0105]
[0106] Combining Examples 1-8 and Comparative Example 1, and referring to Table 2, it can be seen that adding the first thermally conductive filler and the second thermally conductive filler into the polyurethane thermally conductive structural adhesive as in Examples 1-8 can make the structural adhesive have a higher thermal conductivity and increase the hardness of the structural adhesive.
[0107] In combination with Examples 1-8 and Comparative Example 1, and referring to Table 2, it can be seen that adding phase change resin to the polyurethane thermal conductive structural adhesive as in Examples 1-8 has no effect on the peel strength of the thermal conductive structural adhesive at 25°C. However, at 150°C, the phase change resin undergoes a phase change and liquefies and penetrates into the bonding surface of the structural adhesive, thereby weakening the surface bonding strength between the structural adhesive and the object, which is conducive to the peeling of the structural adhesive.
[0108] In combination with Example 1, Example 3, Example 5 and Example 7, and referring to Table 2, it can be seen that the phase change resins in Examples 1, 3, 5 and 7 are all phase change polyolefins, and the phase change temperature of the phase change polyolefins used is 150°C, and the amount of phase change polyolefins in Examples 1, 3, 5 and 7 increases successively. Therefore, when the phase change temperature is reached, the amount of phase change polyolefins that can penetrate into the surface of the structural adhesive increases, and therefore the peel strength of the polyurethane structural adhesive in Examples 1, 3, 5 and 7 at 150°C decreases successively.
[0109] In combination with Example 2, Example 4, Example 6 and Example 8, and referring to Table 2, it can be seen that the phase change resins in Examples 2, 4, 6 and 8 are all phase change paraffins with a phase change temperature of 80°C, and the dosage increases successively. Therefore, when the polyurethane structural adhesive reaches 150°C, the amount of phase change paraffin that can penetrate into the surface of the structural adhesive increases. Therefore, the peel strength of the polyurethane structural adhesive in Examples 2, 4, 6 and 8 at 150°C decreases successively.
[0110] Combining Example 1 and Example 2, Example 3 and Example 4, Example 5 and Example 6, Example 7 and Example 8, and referring to Table 2, it can be seen that adding phase change paraffin with a phase change temperature of 80°C has lower peel strength at 150°C than adding phase change polyolefin with a phase change temperature of 150°C.
[0111] Combining Example 1 and Example 2, Example 3 and Example 4, Example 5 and Example 6, Example 7 and Example 8, and referring to Table 2, it can be seen that using diphenylmethane diisocyanate as a chain extender can reduce the hardness of the polyurethane thermal conductive structural adhesive compared to using polymeric isocyanate.
[0112] In combination with Examples 1-8 and referring to Table 2, it can be seen that compounding 70 μm aluminum hydroxide with 5 μm aluminum oxide, or compounding 50 μm aluminum hydroxide with 1 μm aluminum hydroxide, can both improve the thermal conductivity of the polyurethane thermal conductive structural adhesive.
[0113] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.
Claims
1. A detachable polyurethane thermal conductive structural adhesive, characterized in that: It includes a thermally conductive resin part and a thermally conductive curing agent part, wherein the thermally conductive resin part includes a resin mixture and a first thermally conductive filler, the thermally conductive curing agent includes a curing agent mixture and a second thermally conductive filler, and the volume ratio of the thermally conductive resin part to the thermally conductive curing agent part is 9 / 10-10 / 9; The resin mixture includes a phase change resin, a catalyst and a hydroxy resin M, and the phase change resin accounts for 24-52% by weight of the resin mixture; the phase change resin includes one or more of a phase change polyolefin and a phase change paraffin, and the hydroxy resin M is one or more of a polyether polyol, a polyester polyol, castor oil, a modified castor oil and sorbitol; The curing agent mixture includes a hydroxyl resin N and a chain extender, wherein the hydroxyl resin N accounts for 50-90% by weight of the curing agent mixture; the hydroxyl resin N is one or more of polyether polyol, polyester polyol, castor oil, modified castor oil and sorbitol, and the chain extender is an isocyanate chain extender; In terms of weight percentage of the thermally conductive resin portion, the resin mixture accounts for 3-19%, and the first thermally conductive filler accounts for 81-97%; Calculated by weight percentage of the thermally conductive curing agent portion, the curing agent mixture accounts for 7%-27%, and the second thermally conductive filler accounts for 73%-93%.
2. The detachable polyurethane thermal conductive structural adhesive according to claim 1, characterized in that: The isocyanate chain extender is selected from one or more of diphenylmethane diisocyanate, isophorone diisocyanate and hexamethylene diisocyanate.
3. The detachable polyurethane thermal conductive structural adhesive according to claim 1, characterized in that: The isocyanate chain extender is selected from polyisocyanates.
4. The detachable polyurethane thermal conductive structural adhesive according to claim 1, characterized in that: The phase change temperature of the phase change resin is 80-150°C.
5. The detachable polyurethane thermal conductive structural adhesive according to claim 1, characterized in that: The number average molecular weight of the phase change polyolefin is 2000-5000.
6. The detachable polyurethane thermal conductive structural adhesive according to claim 1, characterized in that: The catalyst is one or more of an organic tin catalyst, an organic zinc catalyst, an aliphatic amine catalyst, an alicyclic amine catalyst, an alcohol compound catalyst and an aromatic amine catalyst.
7. The detachable polyurethane thermal conductive structural adhesive according to claim 1, characterized in that: The first thermally conductive filler and the second thermally conductive filler both include two thermally conductive powders with different particle sizes, and the particle size of one thermally conductive powder is 7-14 times that of the other thermally conductive powder.
8. The detachable polyurethane thermal conductive structural adhesive according to claim 7, characterized in that: The thermally conductive powder is selected from one or more of aluminum hydroxide, aluminum oxide, boron nitride and aluminum nitride.
9. The detachable polyurethane thermal conductive structural adhesive according to claim 1, characterized in that: The first thermally conductive filler further comprises 0.14-0.16% of a first coupling agent in terms of weight percentage of the thermally conductive resin portion; and the second thermally conductive filler further comprises 0.14-0.16% of a second coupling agent in terms of weight percentage of the thermally conductive curing agent portion.
10. The detachable polyurethane thermal conductive structural adhesive according to claim 9, characterized in that: The first coupling agent and the second coupling agent are both selected from one or more of octyltrimethoxysilane, decyltrimethoxysilane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane and 3-glycidyloxypropyltrimethoxysilane.
11. A method for preparing a detachable polyurethane thermal conductive structural adhesive according to any one of claims 1 to 10, characterized in that: The following steps are involved: Mixing the hydroxy resin M, the phase change resin and the catalyst to prepare a resin mixture; Mixing the resin mixture with the first thermally conductive filler to prepare a thermally conductive resin part; Mixing the hydroxy resin N and the chain extender to prepare a curing agent mixture; mixing the curing agent mixture with the second thermally conductive filler to prepare a thermally conductive curing agent part; The thermally conductive resin part and the thermally conductive curing agent part are mixed in a volume ratio of 9 / 10-10 / 9 to prepare a detachable polyurethane thermally conductive structural adhesive.
12. The method for preparing a detachable polyurethane thermal conductive structural adhesive according to claim 11, characterized in that: During the step of mixing the hydroxy resin N and the chain extender to prepare a curing agent mixture, the hydroxy resin N and the chain extender are mixed evenly and then stirred at a constant temperature for reaction.
13. The method for preparing a detachable polyurethane thermal conductive structural adhesive according to claim 12, characterized in that: During the constant temperature stirring reaction, the constant temperature stirring reaction temperature is controlled to be 70-85° C., and the constant temperature stirring reaction time is controlled to be 2-3 h.
Citation Information
Patent Citations
Structural heat-conducting adhesive and preparation method thereof
CN111944458A
Method for manufacturing printed matter and system for manufacturing printed matter
CN113495464A
Cited By
Thermal stripping structural adhesive for battery pack CTP structure and preparation method of thermal stripping structural adhesive
CN122381761A